A taxonomic survey of the genus Vitis L. (Vitaceae) in Italy, with special reference to Elba Island (Tuscan Archipelago) - Ardenghi, Nicola M.g.; Galasso, Gabriele; Banfi, Enrico; Zoccola, Antonio; Foggi, Bruno; Lastrucci, Lorenzo (Phytotaxa, 2014)
As resulted from recent floristic investigations conducted in southern and central Europe, the genus Vitis proved to be, in these areas, an intricate critical group, whose interpretation, often influenced by ampelographic approaches, needed to be clarified in a strict taxonomic sense. The current paper analyzes the taxonomy and the distribution of seven taxa recorded in Italy and assigns new names to three nothospecies, naturalized and/or invasive in additional European countries: V. ×instabilis (= V. riparia × V. rupestris), V. ×koberi (= V. berlandieri × V. riparia), V. ×ruggerii (= V. berlandieri × V. rupestris). Nomenclatural and systematic aspects regarding V. vinifera are also discussed. Original and detailed descriptions, identification keys, illustrations and information on distribution and ecology are provided.